Higher Dosage of Ciprofloxacin Necessary in Critically Ill Patients: A New Dosing Algorithm Based on Renal Function and Pathogen Susceptibility. Issue 4 (15th May 2020) - Gieling, Emilie M.; Wallenburg, Eveline; Frenzel, Tim; de Lange, Dylan W.; Schouten, Jeroen A.; ten Oever, Jaap; Kolwijck, Eva; Burger, David M.; Pickkers, Peter; ter Heine, Rob; Brüggemann, Roger J. M.
Abstract : The objective of the present study was to develop a dosing algorithm for ciprofloxacin based on both renal function and pathogen susceptibility in critically ill patients. In this observational prospective multicenter pharmacokinetic study, a total of 39 adult intensive care unit patients receiving ciprofloxacin were included. On two occasions a total of 531 samples of ciprofloxacin were collected. Renal function is a significant covariate on ciprofloxacin clearance. A dose of 400 mg every 12 hours was sufficient to reach the preestablished target of area under the curve (AUC) in relation to the minimum inhibitory concentration (MIC) (AUC/MIC) > 125 in patients with an estimated glomerular filtration rate (eGFR) < 130 mL/min and an infection caused by a pathogen with an MIC ≤ 0.125 mg/L. For patients with infections caused by pathogens with an MIC ≥ 0.5 mg/L and eGFR> 100 mL/min, doses up to 600 mg four times daily or more were estimated to be required. This study provides a new dosing algorithm for ciprofloxacin in critically ill patients. In order to achieve adequate target attainment, the dosing of ciprofloxacin should be based on renal function and the MIC of the causative pathogen. Higher doses than the standard licensed dose are necessary to obtain target attainment for less susceptible pathogens and patients with high renal clearance. In the setting of impaired renal function, a daily dose of 400 mg (which is currently recommended) will not result in adequate target attainment for less susceptible pathogens.